Potential extract of red algae (Euchema spinosum) on wound healing: literature review: Potensi ekstrak alga merah (Euchema spinosum) terhadap penyembuhan luka: kajian pustaka - Akbar; Fitri; Tsania Himayanti; Fakhrina Fathu Rahman; Choirunnisa Basnawi; Nurul Hasrul; Irfan Sugianto (Makassar Dental Journal PDGI Makassar, 2022)
ABSTRACT Indonesia is a country that has the highest marine species richness; even 45% of the world's seaweed species. One type of sea-weed that is cultivated in Indonesia is red algae (Eucheuma spinosum) which is able to produce active metabolites that have bio-logical activities such as antiviral, antioxidant, antifungal,antibacterial, and anti-inflammatory. This literature review discusses the potential of red algae extract on wound healing, namely secondary data and literature studies, analyzed descriptively by descri-bing and comparing the results of research regarding the active compound content of red algae which is closely related towound healing. It is discussed about various active compounds such as flavonoids, triterpenoids, alkaloids, ascorbic acid, steroids, sa-ponins, and polyphenolsfound in the red algae have antioxidant properties that can accelerate wound healing. It is concluded that the active compounds of flavonoids, triterpenoids,alkaloids, ascorbic acid, steroids, saponins, and polyphenols contained in the red algae have antioxidant properties that can accelerate wound healing.